Ethnomedicinal and ecological status of plants in Garhwal Himalaya, India - Sheikh Mehraj A; Kumar Munesh; Bussmann Rainer W (BMC, 2011)
Abstract Background The northern part of India harbours a great diversity of medicinal plants due to its distinct geography and ecological marginal conditions. The traditional medical systems of northern India are part of a time tested culture and honored still by people today. These traditional systems have been curing complex disease for more than 3,000 years. With rapidly growing demand for these medicinal plants, most of the plant populations have been depleted, indicating a lack of ecological knowledge among communities using the plants. Thus, an attempt was made in this study to focus on the ecological status of ethnomedicinal plants, to determine their availability in the growing sites, and to inform the communities about the sustainable exploitation of medicinal plants in the wild. Methods The ecological information regarding ethnomedicinal plants was collected in three different climatic regions (tropical, sub-tropical and temperate) for species composition in different forest layers. The ecological information was assessed using the quadrate sampling method. A total of 25 quadrats, 10 × 10 m were laid out at random in order to sample trees and shrubs, and 40 quadrats of 1 × 1 m for herbaceous plants. In each climatic region, three vegetation sites were selected for ecological information; the mean values of density, basal cover, and the importance value index from all sites of each region were used to interpret the final data. Ethnomedicinal uses were collected from informants of adjacent villages. About 10% of inhabitants (older, experienced men and women) were interviewed about their use of medicinal plants. A consensus analysis of medicinal plant use between the different populations was conducted. Results Across the different climatic regions a total of 57 species of plants were reported: 14 tree species, 10 shrub species, and 33 herb species. In the tropical and sub-tropical regions, Acacia catechu was the dominant tree while Ougeinia oojeinensis in the tropical region and Terminalia belerica in the sub-tropical region were least dominant reported. In the temperate region, Quercus leucotrichophora was the dominant tree and Pyrus pashia the least dominant tree. A total of 10 shrubs were recorded in all three regions: Adhatoda vasica was common species in the tropical and sub-tropical regions however, Rhus parviflora was common species in the sub-tropical and temperate regions. Among the 33 herbs, Sida cordifolia was dominant in the tropical and sub-tropical regions, while Barleria prionitis the least dominant in tropical and Phyllanthus amarus in the sub-tropical region. In temperate region, Vernonia anthelmintica was dominant and Imperata cylindrica least dominant. The consensus survey indicated that the inhabitants have a high level of agreement regarding the usages of single plant. The index value was high (1.0) for warts, vomiting, carminative, pain, boils and antiseptic uses, and lowest index value (0.33) was found for bronchitis. Conclusion The medicinal plants treated various ailments. These included diarrhea, dysentery, bronchitis, menstrual disorders, gonorrhea, pulmonary affections, migraines, leprosy. The ecological studies showed that the tree density and total basal cover increased from the tropical region to sub-tropical and temperate regions. The species composition changed with climatic conditions. Among the localities used for data collection in each climatic region, many had very poor vegetation cover. The herbaceous layer decreased with increasing altitude, which might be an indication that communities at higher elevations were harvesting more herbaceous medicinal plants, due to the lack of basic health care facilities. Therefore, special attention needs to be given to the conservation of medicinal plants in order to ensure their long-term availability to the local inhabitants. Data on the use of individual species of medicinal plants is needed to provide an in-depth assessment of the plants availability in order to design conservation strategies to protect individual species.